Analysis of Pressure and Flow Patterns on Two-Phase (Air-Water) Flow in Horizontal Pipes With Scalloped Groove - Bachri, Gufron Saiful; Soenoko, Rudy; Widhiyanuriyawa, Denny (Institut Teknologi Dirgantara Adisutjipto, 2019)
The groved surfaces are widely researched to reduce pressure drop and control a flow on the surface. In applicative fluids flow is turbulen. So, the grove addition capable of affecting the boundary layer condition near the wall pipes. This will greatly determine the pressure drop and the flow patterns that occur during the fluids flow. The purpose of this researched is to analyse the impact of the number of grooves in pipes against the pressure drop and the occurred flow patterns. In this researched, we used 3 pipes, which total of grooves were 4,8,16 and the pipes without grooves that used as comparator. The observed flow was two phases flow ( air-water). The researched pipes used acrylic pipes with diameter of 1 inch and length of 100 cm with the groove used was type of scalloped groove. Pressure drop occurs in all of the grooves ; 4,8, and 16. The highest pressure drop decrease occurred in groove 16. When there was drop in pressure drop in every single of groove, in low air discharge, bubbly that firmed was more tightly without making slug flow. When the debit was getting bigger, the bubbly was reduced and followed by the emergence of slug flow. The changes in water debit in the decrising of pressure drop in every single of drop, shows the dencity between the bubbly and slug flow that firmed